Tacrolimus Therapy Among Steroid-Resistant Nephrotic Syndrome Children: A Preliminary Study in West Java, Indonesia - Widiasta, Ahmedz; Wahyudi, Kurnia; Rachmadi, Dedi (International Journal of Integrated Health Sciences, 2024)
Objective: To explore the outcomes of Tac therapy for Steroid-Resistant Nephrotic Syndrome (SRNS) and its implication in reducing the number of CKD events.Methods: An open, prospective, cohort study was conducted at a tertiary hospital in Bandung, West Java, Indonesia. Children (age 1–18 years old) with steroid and cyclophosphamide resistant nephrotic syndrome were enrolled in this study. Blood pressure, urinary protein, serum ureum, and creatinine levels were measured every month, Tac and soluble urokinase plasminogen activator receptor (supaR) levels were assessed at the 0, third, and sixth months.Results: Ten of fifteen subjects enrolled in this study got better within 3–6 months with a trend of decreasing suPAR level and proteinuria, as well as stable blood pressure and serum creatinine and ureum level. During treatment, no side effects of the subjects were found with the Tac level maintain safely.Conclusion: Tac is an effective and safe agent in treating SRNS, especially for those do not respond well to an alkylating agent.